ETHNOGRAPHIC ANALYSIS OF THE SOCIO-CULTURAL CONTENT OF THE MUTUAL ASSISTANCE PRACTICES OF THE KABARDIANS AND BALKARS - SOBLIROVA, Z.H.; HOKONOV, M.A.; ZHURTOVA, A.A. (Kavkazologiya, 2019)
The article deals with the traditional Institute of mutual assistance for the peoples of Kabardino-Balkaria. The norms of mutual assistance determined the internal content of the mechanism of socio-economic interaction in the rigidly institutionalized society of highlanders and leveled its moral flaws. They were an integral part of the people's mentality and embodied the precedent of social order, stability and self-organization. The combination of stability and dynamics of traditions of mutual assistance ensured the transfer of ethno-genetic empathic complex of culture to the younger generation. In the folk art of Kabardians and Balkarians there are many examples of agricultural and economic interaction and implicative pre-religious types of assistance. Ethical obligations contributed to the improvement of the economic potential of small Patriarchal-tribal farms of the highlanders. Forms and types of mutual support functioned as a whole system and were voluntary. The need to perform a large amount of heavy agricultural work in a limited time required the unification of labor efforts of the whole village. During the Soviet period, the institution of mutual assistance suffered changes and was included in the process of forming the state social security system.